2012
DOI: 10.1097/dad.0b013e31823adf0e
|View full text |Cite
|
Sign up to set email alerts
|

Pure Apocrine Nevus

Abstract: Apocrine nevus is a rare tumor composed of increased mature apocrine glands and ductal structures within a fibrous stroma, located predominantly in the reticular dermis. They have been reported in association with apocrine carcinoma, extramammary Paget disease, and syringocystadenoma papilliferum; less commonly a pure apocrine nevus is identified, unassociated with another apocrine proliferation. Clinically apocrine nevi may appear as solitary or multiple nodules or plaques on the scalp, presternal skin, thoug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…3 A marked male predominance of 9:1 has been reported in previous studies, including cases of AGH/AN seen in the axillae. 3 Our study also revealed that all four lesions were on the axillae of men. The location of the axilla may result in another problem; it can be clinicopathologically difficult to distinguish AGH/AN from supernumerary mammary tissue.…”
mentioning
confidence: 63%
See 4 more Smart Citations
“…3 A marked male predominance of 9:1 has been reported in previous studies, including cases of AGH/AN seen in the axillae. 3 Our study also revealed that all four lesions were on the axillae of men. The location of the axilla may result in another problem; it can be clinicopathologically difficult to distinguish AGH/AN from supernumerary mammary tissue.…”
mentioning
confidence: 63%
“…This study was approved by research ethics committees of Shizuoka Cancer Center Hospital, Sunto, Japan (reference number: T2023-10), Komagome Hospital, Tokyo, Japan (reference number: 3161), Osaka International Cancer Institute, Osaka, Japan (reference number: 23079), Kagoshima Medical Center, Kagoshima, Japan (reference number: 2023-COI-3), and Shinshu University School of Medicine, Matsumoto, Japan (reference number: 5907). Keisuke Goto MD 1,2,3,4,5,6,7,8,9 Yukiko Kiniwa MD, PhD 10…”
Section: Acknowledgmentsmentioning
confidence: 99%
See 3 more Smart Citations